Teori Strategi Kampanye Aktor: Analisis Kasus Kemenangan Emmanuel Macron Pada Pemilihan Presiden Prancis 2017 - Lase, Iwan Krisman; Amin, Muryanto; Ritonga, Alwi Dahlan (Talenta Publisher, 2023)
The year 2017 was the year in which the French state held presidential elections which are held every five years. Presidential elections in France are referred to as Executive elections. Executive elections are held to elect Président de la République dan Prémier Minister. The issue of frexit, the issue of immigrants, and the issue of the economy became the main themes used by the candidates in their campaigns. After going through a fierce battle since the first round and continuing in the second round of the French presidential election, Emmanuel Macron won the election with a landslide victory over Marine Le Pen. This research aims to describe and analyze Emmanuel Macron's campaign strategy in the 2017 French presidential election. The method used in this research is a qualitative method with a descriptive type of research to describe in detail the subject being studied. The campaign strategy used by Emmanuel Macron is the Framing Strategy and Persuading Strategy. Macron presents counter framing by making voters afraid of the figure of Le Pen who cannot properly calculate the impact of his program, this is what Macron calls the spirit of defeat or The Spirit of Death. The Spirit of Conquest, which Macron mentions to name his vision and mission in leading France, is a persuasive strategy that Macron uses to convince voters that the interests of French citizens will be in line with his programs.